2014
DOI: 10.1186/1471-2407-14-867
|View full text |Cite
|
Sign up to set email alerts
|

Validation of COL11A1/procollagen 11A1 expression in TGF-β1-activated immortalised human mesenchymal cells and in stromal cells of human colon adenocarcinoma

Abstract: BackgroundThe human COL11A1 gene has been shown to be up-regulated in stromal cells of colorectal tumours, but, so far, the immunodetection of procollagen 11A1, the primary protein product of COL11A1, has not been studied in detail in human colon adenocarcinomas. Some cancer-associated stromal cells seem to be derived from bone marrow mesenchymal cells; the expression of the COL11A1 gene and the parallel immunodetection of procollagen 11A1 have not been evaluated in these latter cells, either.MethodsWe used qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 46 publications
4
26
0
1
Order By: Relevance
“…Moreover, COL11A1 with a high level of OH-Lys was expressed only in CRC ECM ( Fig. 4E ), in agreement with a report showing COL11A1 to be produced by cancer-associated myofibroblasts and not expressed in the healthy colon 33 .…”
Section: Resultssupporting
confidence: 92%
“…Moreover, COL11A1 with a high level of OH-Lys was expressed only in CRC ECM ( Fig. 4E ), in agreement with a report showing COL11A1 to be produced by cancer-associated myofibroblasts and not expressed in the healthy colon 33 .…”
Section: Resultssupporting
confidence: 92%
“…Several studies reported that COL11A1 is overexpressed in invasive ductal carcinoma (IDC) of the breast relative to ductal carcinoma in situ (DCIS) in Spanish populations. This overexpression is correlated with carcinoma aggressiveness, progression, and lymph node metastasis22. Chang et al .…”
Section: Discussionmentioning
confidence: 99%
“…as they undergo epithelial-to-mesenchymal transition (EMT). It appears that TGF-beta signaling plays an important role in the transformation, as we had speculated by the prominent presence of related genes INHBA and THBS2 (1), and as also proposed by various studies (14,46,47).…”
Section: Breast Cancermentioning
confidence: 53%